1999
DOI: 10.3171/jns.1999.90.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression of cranial nerves: lessons learned after 4400 operations

Abstract: Using the techniques described in this report, microvascular decompression is an extremely safe and effective treatment for many cranial nerve rhizopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(159 citation statements)
references
References 11 publications
3
148
0
8
Order By: Relevance
“…In table 3, we compared the clinical results of our patients with previously reported results of DFP patients who underwent MVD for HFS. Although facial spasm completely disappeared after MVD, delayed facial weakness may decrease the patient’s individual satisfaction [1,5,7,38,39,40]. With delayed facial weakness after surgery, relevant explanations have been introduced including reactivation of HSV, delayed facial nerve edema due to unwanted inflammation, and microcirculation disruptions due to an ischemic result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In table 3, we compared the clinical results of our patients with previously reported results of DFP patients who underwent MVD for HFS. Although facial spasm completely disappeared after MVD, delayed facial weakness may decrease the patient’s individual satisfaction [1,5,7,38,39,40]. With delayed facial weakness after surgery, relevant explanations have been introduced including reactivation of HSV, delayed facial nerve edema due to unwanted inflammation, and microcirculation disruptions due to an ischemic result.…”
Section: Discussionmentioning
confidence: 99%
“…Hemifacial spasm (HFS) is a functional disorder characterized by twitching of the muscles innervated by the facial nerve. MVD is a highly accepted and effective method for the treatment of patients with HFS with an operative morbidity of less than 10% [5,6,7,8]. The risks of the operation are generally related to the surgical approach and particularly to surgery on the seventh nerve [2].…”
Section: Introductionmentioning
confidence: 99%
“…material, see www.karger.com?doi=10.1159/000342795), the patient’s head is secured in a Mayfield 3-pin head clamp. We use the Mayfield clamp technique and positioning described by McLaughlin et al [22]. The following landmarks should be noted prior to prepping: the tip of the mastoid process, the insertion of the digastric muscle, and the course of the sigmoid and transverse sinus as described by McLaughlin et al [22] (fig.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In the study by Defazio et al [7], 70 of 86 patients continued botulinum toxin injections and 2 (2.3%) experienced complete and long-lasting relief of symptoms. In cases of patients treated with MVD, many researchers report a success rate of approximately 85-95% postoperatively [1,8,10,12]. In other words, this means 5-15% of MVD patients experience remission.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have found treatment with medications unsatisfactory [3,5]. On the other hand, many studies have established the efficacy of botulinum toxin therapy or microvascular decompression (MVD) in the treatment of HFS [3,4,5,6,7,8,9,10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%